EKO-TEOLOGI AL-QUR`AN: SEBUAH KAJIAN TAFSIR AL-QUR`AN DENGAN PENDEKATAN TEMATIK - Wardani, Mulyani dan (Jurnal Ilmu Ushuluddin, 2013)
One of the important issues facing the global and human was the environmental issue. This paper discussed a solution to this global crisis from the perspective of al-Qur`an about theology environment (eco - theology). By applying a thematic approach (mawdhÃ»Ã®) in the study of Tafseer al-Qur`an, this paper came to an important conclusion. First, in view of universe al-Qur`an was referred to as evidence of Gods creation creativity. Nature was also created as a sign of his power. Therefore, the universe was created had a purpose (bil hikmah) (bi al-haq), not in vain (falsehood). Second, al-Qur`an taught theological principles in the maintenance of nature, namely that the Earth was only inherited theological promised by His servants the righteous course, the relationship management of nature (taskhÃ®r) with a value of tawhid, the need to pay attention to the balance of the cosmos and the principle economic in nature management, the necessity of the earth "prospered" (i`mar), and the prohibition of destructive nature. Third, al-Qur`an stated that people who did not believe âkeberhikmahanâ universe, theologically, was a disbeliever , because at the same time he believed the futility of Gods creation, so the implications are more far in the denial of moral obligation (moral imperative) and blindness spiritual (spiritual blindness). The commentators understood the "kufr ecological" implied a denial of the divinity of God Almighty and the denial of the resurrection in the afterlife.